"Parent Advocacy" as an Ideological Code: LGBTQ Parents Engage with Disability Services. Issue 1 (2nd January 2019) - Gibson, Margaret F.
ABSTRACT: What does the work that LGBTQ parents do to find resources for their disabled children reveal about the social organization of services? This article presents findings from an institutional ethnography study based on interviews with 15 lesbian, gay, bisexual, transgender, and/or queer (LGBTQ) parents and six key community informants in Toronto, Canada. The analysis focused on the work parents did to engage with disability service systems on behalf of their children, and the ways in which families' social privilege and/or marginalization affected their experiences. Particular attention was paid to the ways in which "parent advocacy" was taken up, responded to, and critiqued in these interviews. "Parent advocacy" was found to operate as what Dorothy Smith has called an "ideological code" (Smith 1999), offloading systemic responsibilities onto parents, shielding inequities, and promoting individualized competition between service users. This study suggests that the systemic organization that makes "parent advocacy" necessary also renders parents' relative privilege or marginality central to what their children receive.